2020
DOI: 10.1111/gtc.12771
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human‐induced pluripotent stem cells carrying homozygous RB1 gene deletion

Abstract: Retinoblastoma is an infant cancer that results from loss of RB1 expression in both alleles. The RB1 gene was the first reported cancer suppressor gene; however, the mechanism by which RB1 loss causes cancer in the retina has not yet been clarified. Human‐induced pluripotent stem cells (iPSCs) provide an ideal tool for mechanistic research regarding retinoblastoma. However, because RB1 is a tumor suppressor, loss of both alleles of RB1 in human iPS cells may affect the phenotype of the cells. To examine this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Here, we designed gRNAs to target exon‐SA and ‐SD sites. We previously constructed a plasmid contains tandem‐two gRNAs, and this worked well 41 . The two gRNAs remove exons by targeting both ends of an intron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we designed gRNAs to target exon‐SA and ‐SD sites. We previously constructed a plasmid contains tandem‐two gRNAs, and this worked well 41 . The two gRNAs remove exons by targeting both ends of an intron.…”
Section: Discussionmentioning
confidence: 99%
“…We previously constructed a plasmid contains tandem-two gRNAs, and this worked well. 41 The two gRNAs remove exons by targeting both ends of an intron. If single-nucleotide polymorphism data are available, it is possible to target a single-nucleotide polymorphism to one allele when designing an allele-specific exon-skipping vector; this would effectively and safely "cure" mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoblastoma is a childhood cancer of the developing retina that starts with biallelic inactivation of the retinoblastoma gene 1 (RB1) gene [ 108 , 109 ]. Children with germline mutations in RB1 have an increased risk of developing retinoblastoma and other cancers later in life.…”
Section: Construction Of Organoids Based On Ipsc Technologymentioning
confidence: 99%
“…ROs have also been used to identify the disease mechanisms of Leber’s congenital amaurosis (LCA)-related RPE65 (Li et al 2019 ), CEP290 ( Shimada et al 2017 ) , AIPL1 (Lukovic et al 2020 ) and CRX (Kruczek et al 2021 ). Other ocular diseases, such as glaucoma (VanderWall et al 2020 ), macular telangiectasia type 2 (Gantner et al 2019 ), microphthalmia (Eintracht et al 2020 ), retinoblastoma (Deng et al 2020 ; Liu et al 2020 ; Saengwimol et al 2020 ), Stargardt disease (Khan et al 2020 ) and RS1- related X-linked juvenile retinoschisis as a model, moreover, a study on syndrome coronavirus 2 (SARS-CoV-2) demonstrated that SARS-CoV-2 can infect the retinal cells (Ahmad Mulyadi Lai et al 2021 ). All these studies have been conducted in the last 4 years and have increased over time, which highlights the potential of RO as a model for retinal development and diseases.…”
Section: Main Textmentioning
confidence: 99%